Body mass index and risk of colorectal cancer according to tumor lymphocytic infiltrate. Issue 4 (10th May 2016) - Hanyuda, Akiko; Ogino, Shuji; Qian, Zhi Rong; Nishihara, Reiko; Song, Mingyang; Mima, Kosuke; Inamura, Kentaro; Masugi, Yohei; Wu, Kana; Meyerhardt, Jeffrey A.; Chan, Andrew T.; Fuchs, Charles S.; et al.
Abstract : Higher body mass index (BMI), higher body adiposity and obesity have been associated with increased risk of colorectal cancer. Evidence suggests that excess energy balance may influence systemic immune and inflammatory status. Thus, we hypothesized that the positive association between BMI and colorectal cancer risk might differ according to colorectal carcinoma subtypes according to levels of histopathological lymphocytic reaction to tumor. We collected biennial questionnaire data on weight and baseline height information in two prospective cohort studies, the Nurses' Health Study (1980‐2010) and the Health Professionals Follow‐up Study (1986‐2010). Utilizing duplication‐method Cox proportional hazards regression models, we prospectively assessed the association between BMI and risk of colorectal cancer subtypes according to the degree of Crohn's‐like lymphoid reaction, peritumoral lymphocytic reaction, intratumoral periglandular reaction, tumor‐infiltrating lymphocytes, the overall lymphocytic reaction score, or T‐cell [CD3 +, CD8 +, CD45RO (PTPRC) + or FOXP3 + ] density in tumor tissue. Statistical significance level was adjusted for multiple hypotheses testing by Bonferroni correction. During follow up of 1, 708, 029 men and women (over 3, 346, 752 person‐years), we documented 1, 436 incident rectal and colon cancer cases with available formalin‐fixed paraffin‐embedded tumor tissue materials and pathological immunity data. BMI was significantly associated with higher risk of overall colorectal cancer (Ptrend < 0.001); however, the association of BMI with colorectal carcinoma risk did not significantly differ by the level of lymphocytic reaction or T‐cell infiltration in tumor tissue status (Pheterogeneity > 0.10). BMI may be associated with risk of colorectal cancer regardless of levels of lymphocytic response to tumor. Abstract : What's new? A vigorous immune response does not particularly hinder obesity‐related cancer, according to new results. Being fat increases risk of colorectal cancer and a vigorous T‐cell response can improve colorectal cancer prognosis. These authors suspected that immune cells around the tumor may suppress the oncogenic pathway induced by excess fat. Using data from the Nurses' Health Study and the Health Professionals Follow‐up Study, they investigated whether the impact of BMI varied depending on the degree of lymphocytic infiltration. BMI association with colorectal cancer, they determined, did not vary with lymphocytic reaction or the density of T‐cells infiltrating the tumor tissue.